FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM BERWIRAUSAHA - Daud Fiqo Ghafika; Maria Ulfah; Yusawinur Barella; Sri Buwono; M Zainul Hafizi (Program Studi PGSD Universitas Flores, 2024)
To support and enhance the human resources of students in entrepreneurship and their ability to create new job opportunities, good preparation and individual business interest are required. This study aims to identify the intrinsic and extrinsic factors that influence the entrepreneurial interest of students in the Social Studies Education Program at FKIP Universitas Tanjungpura. The research employs a qualitative approach with a case study on five Social Studies students from the 2020-2022 cohorts who have been involed in entrepreneurial activities. The main findings highlight the backgrounds of these individuals in starting their businesses, which include intrinsic factors such as personal experience, internal motivation, a sense of enjoyment, and mental preparedness, as well as extrinsic factors such as the family environment and residential surroundings. The impact of this research is a deep understanding of the motivations behind the entrepreneurial interest of Social Studies student, which can provide valuable insights for the development of entrepreneurship programs in academic settings.